HUBUNGAN ASUPAN PROTEIN, LEMAK, KALIUM DAN MAGNESIUM DENGAN TEKANAN DARAH SISTOLIK DAN DIASTOLIK LANJUT USIA - Menad M, Aria; Kusumastuti, Aryu Candra (Departemen Ilmu Gizi, Fakultas Kedokteran, Universitas Diponegoro, 2017)
Background : Hypertension is one of the degenerative diseases that has high prevalence an increase. One of the factors that influence blood pressure in hypertensive patients is protein, fat, potassium, and magnesium intake. The purpose of this study was to determine the relationship of protein, fat, potassium, and magnesium intake with blood pressure in elderly.Design : This cross-sectional study was conducted among 42 subjects (aged 60-80 years) of PWRI (Persatuan Wredatama Republik Indonesia) members rating South Semarang, Semarang. Food recall method was used to measure the intake of protein, fat, potassium and magnesium intake. Blood pressure was measured with a mercury sphygmomanometer. Rank- Spearman test was used on bivariate analysis. Results : On the results of this study as many as 83.3% of subjects hypertention. Protein intake (52.4% of subjects), fat intake (100% of subject) potassium intake (54.8%) and magnesium (95.2% of subjects) are lower than needs. Bivariate analysis shows that there were no correlation between protein, fat, potassium, and magnesium intake and systolic blood pressure and diastolic blood pressure. Conclusion : In there were correlation between protein, fat, potassium, and magnesium intake and systolic blood pressure and diastolic blood pressure.Â